Moral Education in Strengthening Teachers' Spiritual Values from The Perspective of The Qodiriyah Wa Naqsabandiyah Tarekat - Lutfi, Muhammad Khoirul; Maimun, Agus; Padil, Moh.; Barizi, Ahmad; Masuwd, Mowafg Abrahem (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2025)
This investigates moral education through spiritual reinforcement of teachers in the Qodiriyah wa Naqsyabandiyah Tarekat at MA Darul Ulum Karangpandan, Pasuruan, addressing contemporary moral degradation in formal education. Employing qualitative case study methodology with triangulated data collection, the research is grounded in the theo-anthropocentric paradigm and Islamic intellectual traditions. Three principal findings emerged. First,